Determinants of Personal Risk Financing Strategies - Brokesova, Zuzana; Ondruska, Tomas; Pastorakova, Erika (Ekonomický časopis/Journal of Economics, 2025)
Adverse income shocks may have an eminent effect on short-term and long-term financial stability of individuals and households. Optimal response to risk exposure is driven by effectively chosen risk management strategies through combination of insurance, savings and other tools. However, individuals and households do not always make optimal decisions in these situations. The paper investigates the determinants of individuals’ decisions on the implementation of risk financing strategies. We test demographic, economic, and personal characteristics (including risk attitude and financial literacy) with the aim to identify relevant factors associated with different personal risk management behaviour. We use data from the survey in the Slovak Republic. We analyse the use of the two risk financing strategies, risk transfer and self-insurance, in coping with life and health risks of individuals. Our results show that level of financial literacy and risk attitude are important elements in personal risk management decisions, which policy-makers should also reflect on in an effort to ensure the financial stability of individuals and households.